Standing-based office work shows encouraging signs of attenuating post-prandial glycaemic excursion. Issue 2 (2nd December 2013) - Buckley, John P; Mellor, Duane D; Morris, Michael; Joseph, Franklin
Abstract : Objectives: The main aim of this study was to compare two days of continuous monitored capillary blood glucose (CGM) responses to sitting and standing in normally desk-based workers. Design, setting and participants: This open repeated-measures study took place in a real office environment, during normal working hours and subsequent CGM overnight measures in 10 participants aged 21–61 years (8 female). Main outcomes: Postprandial (lunch) measures of: CGM, accelerometer movement counts (MC) heart rate, energy expenditure (EE) and overnight CGM following one afternoon of normal sitting work compared with one afternoon of the same work performed at a standing desk. Results: Area-under-the-curve analysis revealed an attenuated blood glucose excursion by 43% (p=0.022) following 185 min of standing (143, 95% CI 5.09 to 281.46 mmol/L min) compared to sitting work (326; 95% CI 228 to 425 mmol/L min). Compared to sitting, EE during an afternoon of standing work was 174 kcals greater (0.83 kcals/min; p=0.028). The accelerometer MC showed no differences between the afternoons of seated versus standing work; reported differences were thus a function of the standing work and not from additional physical movements around the office. Conclusions: This is the first known 'office-based' study to provide CGM measures that add some of the needed mechanistic information to the existing evidence-base on why avoiding sedentary behaviour at work could lead to a reduced risk of cardiometabolic diseases.